That time I got reincarnated as a slime. 15 - Fuse (Manga author); Kawakami, Taiki (Kodansha Comics, 2020)
"With the Falmuth army decimated, Rimuru's transformation into a Demon Lord finally begins. A successful evolution would mean unlocking new powers and a chance to resurrect the dead, but as Rimuru and his followers are forced into a deep sleep, the future is all but certain. Fortunately, the mysterious demon Rimuru summoned has every intention of seeing his master return as the slime he always was, no matter the cost..."--Provided by publisher.